PERBEDAAN MEDIA EDUKASI POSCADT DAN POSTER TERHADAP PENGETAHUAN SEKS REMAJA UNTUK PENCEGAHAN KEKERASAN SEKSUAL - Batlajery, Jomima; Nuraini, Novia -; Rajab, Wahyudin; Maryanah, Maryanah; Masitoh, Siti; Nurdahlia, Nurdahlia (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
The incidents of sexual violence in South Jakarta for all groups has doubled from 2021 to 2022, namely from 4,350 to 8,691 cases, including the rapidly growing number of cases of sexual violence against teenagers aged 15-24 years. One factor in efforts to increase teenagers' knowledge about sexual violence is by providing health education to teenagers, such as using posters and podcasts. This research aims to determine the effectiveness of differences in podcast poster media on teenagers' knowledge about sexual violence at Bunda Kandung High School, South Jakarta City. This research is a quantitative research with a quasi-experimental research design (pretest and posttest with control group design). The sample used proportionate sampling with a random sampling system technique of 40 samples for one group. A total of 80 respondents were grouped into two classes, namely poster and podcast media, there was a difference in the final score after the intervention with a p-value of 0.001. The use of podcast media is more effective (47.90 mean rank) compared to poster media (33.10) in increasing teenagers' knowledge. It is hoped that health workers can use media such as posters and podcasts to provide health education and promotion, especially in school areas.